EXPLORING COOPERATIVE PRINCIPLES IN PLASTIC SURGERY PODCAST CONVERSATIONS - Kebar, Metison Ismal; Laksminy, Luh Putu; Agung, I Gusti Ayu Mahatma (LUNAR, 2025)
This study investigates how Grice’s Cooperative Principle and Leech’s Politeness Principle function in unscripted podcast dialogues on the topic of plastic surgery. While these pragmatic frameworks have been widely applied in analyzing spoken interaction, their application in informal digital contexts such as podcasts remains underexplored. Using a descriptive qualitative method, this research analyzes transcripts from two YouTube podcast episodes: Megan Fox: My Plastic Surgery Story by Call Her Daddy and Why We Became Plastic Surgeons by Dr. CalvertTV. The findings reveal that speakers generally adhere to the maxims of quality, quantity, relation, and manner, while also applying politeness strategies including tact, modesty, and agreement. However, instances of flouting were also observed, often serving rhetorical purposes such as humor, emphasis, or the negotiation of sensitive topics. The study concludes that both Gricean and Leechian principles remain relevant in analyzing digital communication. Podcast discourse provides valuable insight into how meaning, relational alignment, and conversational coherence are co-constructed in real-time, shaped by both linguistic choices and social context.